Dinamika Hubungan Kekuasaan antara Dosen Pembimbing dan Mahasiswa dalam Konteks Feodalisme Akademik - Patty, Jusak; Lekatompessy, Felicia Miranda; Lekatompessy, Jeny (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study explores the dynamics of the power relationship between supervisors and students in the context of academic feudalism in Indonesian higher education. This study uses an interpretive phenomenological approach, this study involves in-depth interviews with 10 students of the English Language Education Study Program at Pattimura University. The analysis process is iterative and involves constant comparisons between raw data, themes, and interpretations. The results revealed that students face various challenges due to rigid hierarchical structures, including restrictions on creativity and academic autonomy, communication barriers, inhibitions of critical thinking, and negative psychological impacts. However, students also show resilience by developing strategies such as assertive communication, finding alternative resources, building solidarity between students, negotiation, and compromise, and developing academic independence. These findings suggest a gradual shift in power dynamics in Indonesian higher education, where students are actively negotiating their positions in a hierarchical system. The study highlights the need for institutional reforms, faculty professional development, and student support programs to create a more egalitarian and collaborative academic environment